The application of allelopathy in integrated pest management systems to control temperate European crop pests: a systematic map - Charlotte Kiely; Nicola Randall; Magda Kaczorowska-Dolowry (CABI Agriculture and Bioscience)
Abstract Background Pesticides perform vital roles within agriculture but growing concern for their impact on the environment and non-target organisms has created a market for biopesticides with fewer ecological impacts. One source of biopesticides is allelochemicals, here defined as compounds released by an organism that have an inhibitory or stimulatory effect on neighbouring organisms. The focus of this study is allelopathic plants and their inhibitory effects on invertebrate herbivorous agricultural pests of temperate Europe. A systematic map is required to describe the current state of research and collate evidence. Methods Two academic databases were searched for relevant studies in temperate climates. The results were imported into EPPI-Reviewer, duplicates removed, studies screened and data extracted into a searchable database following the inclusion criteria and coding tool set out in the protocol. Screening consistency was checked at each stage using 5% of the studies. Critical appraisal was not conducted. Each unique combination of key variables (pest, plant, allelochemical, application method, intervention form) was treated as a separate datapoint or experiment. The data was then analysed and cross-tabulated to produce descriptive statistics and heatmaps. Results This systematic map produced a database which included 243 studies containing 717 experiments from 5550 initial results. Research was unevenly distributed among all key variables with a distinct bias towards extracted allelochemical experiments under laboratory conditions. Allyl isothiocyanate was the most studied allelochemical and of the 99 identified chemical groups, flavonoids and glucosinolates were the most frequent. A wide range of pest and plant species were identified. Brassicas were the most studied plant family and Lepidoptera the most studied pest order. Physical living plants, as opposed to plant extracts or isolated allelochemicals, were predominantly studied in terms of resistance. Allelopathy application methods were not specified in the abstract of 22% of experiments and only 10% of experiments were conducted under field conditions. Conclusion Allelopathy has been studied in the context of temperate invertebrate pest control in some breadth but little depth and key pest species have not been targeted. The map highlighted significant gaps in the evidence base and a distinct lack of field studies or studies comparing application methods. It contains insufficient evidence to guide policy or management decisions, but provides a research tool and indicates areas for future studies including highlighting topics for secondary research. Critical appraisal is needed to determine allelopathic affect and future search strings should detail all application methods. Protocol registration The a-priori protocol was peer-reviewed and published through PROCEED (Kiely C, Randall N. Collaboration for Environmental Evidence: PROCEED. How have allelopathic plants been used within integrated pest management systems to control European crop pests in arable and field vegetable systems in temperate climates?: A Systematic Map Protocol. 2022. https://www.proceedevidence.info/protocol/view-result?id=14 . Accessed 5 Jan 2023.).